Benefiting from the natural color of wood in confirming the plastic and expressive values of the sculptural work - Dr. Arfaa shaker hassen (Journal of Architecture, Art & Humanistic Science, 2024)
Tree wood is a natural material that is one of the oldest materials used by the artists of many ancient civilizations, as well as by the sculptors of modern and contemporary arts. In this research, the researcher relied on the natural color of wood, each with its own characteristics. He chose the wood blocks, each by its nature in terms of porosity, color, and different sectors, and tried to employ them to serve the subject of the research. The research, despite the difference in formations between vertical and horizontal, the researcher incited to achieve unity in the artistic work where the use of one raw material and one artistic processors, and he also used the technique of direct carving on wood, with the requirements of each stage of machines